1998
DOI: 10.1038/2048
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of caveolin expression induces androgen sensitivity in metastatic androgen-insensitive mouse prostate cancer cells

Abstract: Although prostate cancer cells are often initially sensitive to androgen ablation, they eventually lose this response and continue to survive, grow and spread in the absence of androgenic steroids. The mechanism(s) that underlie resistance to androgen ablation therapy remain mostly unknown. We have demonstrated that elevated caveolin protein levels are associated with human prostate cancer progression in pathological specimens. Here we show that suppression of caveolin expression by a stably transfected antise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
126
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 166 publications
(132 citation statements)
references
References 8 publications
4
126
2
Order By: Relevance
“…Thompson and coworkers have consistently demonstrated that caveolin-1 expression was associated with progression of human prostate cancer and with primary and metastatic human breast cancer (Nasu et al, 1998;Thompson et al, 1999;Yang et al, 1999Yang et al, , 2000Li et al, 2001;Tahir et al, 2001). Recently the role of caveolin-1 as a tumor promoting factor in prostate cancer epithelial cells has been definitively addressed in vivo using the TRAMP mice model, which is analogous to human prostate tumors (Williams et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Thompson and coworkers have consistently demonstrated that caveolin-1 expression was associated with progression of human prostate cancer and with primary and metastatic human breast cancer (Nasu et al, 1998;Thompson et al, 1999;Yang et al, 1999Yang et al, , 2000Li et al, 2001;Tahir et al, 2001). Recently the role of caveolin-1 as a tumor promoting factor in prostate cancer epithelial cells has been definitively addressed in vivo using the TRAMP mice model, which is analogous to human prostate tumors (Williams et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, in prostate cancer cells, Caveolin-1 specific anti-sense constructs induce cell death after testosterone removal. This effect was abrogated, when the cells were treated with the general caspase inhibitor Z-VAD-FMK [139]. Additionally, in human prostate cancer cells, Caveolin-1 presence favors phenylephrine-induced resistance to thapsigargin mediated cell death.…”
Section: Caveolin-1 and Drug-resistancementioning
confidence: 90%
“…Liganddependent Activation-High levels of caveolin-1 expression have been observed to correlate with the sensitivity of murine metastatic prostate cancer cells to androgen withdrawal (12), a finding that suggests caveolin plays a role in AR signaling. To test this hypothesis, we used a cell culture model to determine whether changes in the levels of caveolin-1 expression alter ligand-dependent AR activation.…”
Section: Overexpression Of Caveolin-1 Enhances Ar-mediated Transcriptmentioning
confidence: 98%
“…Ectopic overexpression of caveolin-1 inhibits Her2/Neu activity in vivo, a further suggestion of a tumor suppressor role of caveolin-1 (26). In cells derived from an mouse prostate reconstitution model, however, overexpression of caveolin-1 promotes resistance to apoptosis induced by androgen withdrawal, suggesting a promoter role of caveolin-1 in prostate tumor progression (12). Steroid hormone estrogen receptors have been shown to be potentiated by caveolin-1 in their transcriptional activities (27).…”
mentioning
confidence: 99%
See 1 more Smart Citation